(untitled) (Bangladesh Journal of Botany, 2021)
Photosynthetic capacity and photosystem II (PSII) activity decreased with increasing temperature, whereas antioxidant enzyme activity showed the opposite trend. High temperature stress induced a significant increase in Φf,D, and D1 protein turnover rate. Photosynthetic capacity, PSII activity, and antioxidant enzyme levels in plants treated at 35 and 40°C were restored to control levels upon stress relief, whereas those in plants grown at 45℃ were only partially restored. Therefore, the temperature limit for heat tolerance in Parthenocissus quinquefolia is between 40 and 45℃. Further, it was observed that antioxidant enzymes were crucial for high-temperature stress resistance in P. quinquefolia, with DEGP1 protein playing a major role in the rapid turnover of D1 protein for PSII repair. Bangladesh J. Bot. 50(2): 433-436, 2021 (June)